2004
DOI: 10.1097/00006676-200410000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic Reaction in Pancreatic Cancer

Abstract: Activated PSCs are present in the stromal reaction in pancreatic cancers and are responsible for the production of stromal collagen. PSC function is influenced by pancreatic cancer cells. Interactions between tumor cells and stromal cells (PSCs) may play an important role in the pathobiology of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
505
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 560 publications
(519 citation statements)
references
References 29 publications
11
505
1
2
Order By: Relevance
“…PSC (on which primary cilia have been detected) have been linked to the initiation of stromal reaction in PDAC and CP [36], therefore it would seem logical that the increase of PC in PDAC and CP stroma may be triggered through pancreatic stellate cells, since these cells also promote tumor cell proliferation [43,52]. This is consistent with our remarkable observation of very long and numerous PC in fibrotic areas/tubular complexes of CP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PSC (on which primary cilia have been detected) have been linked to the initiation of stromal reaction in PDAC and CP [36], therefore it would seem logical that the increase of PC in PDAC and CP stroma may be triggered through pancreatic stellate cells, since these cells also promote tumor cell proliferation [43,52]. This is consistent with our remarkable observation of very long and numerous PC in fibrotic areas/tubular complexes of CP.…”
Section: Discussionsupporting
confidence: 88%
“…Given the PC re-distribution from the epithelium to the stroma, and since pancreatic stellate cells (PSC) play an important role with regard to the desmoplastic stroma-reaction in PDAC [36], we next examined whether PSC express PC and therefore may be able to transfer HH signals. Immunohistochemistry demonstrated that PC are formed by PSC as shown in Fig 7D. …”
Section: Primary Cilia On Pancreatic Stellate Cells and Cancer Cell Lmentioning
confidence: 99%
“…In pancreatic cancer, a dense stroma forms around the tumor cells and collagen synthesis by PSCs increases after exposure to inflammatory cytokines such as TGF-β, TNF-α and IL-10 [31,32]. In fact, prior studies have shown decreased response to gemcitabine and radiation when cancer cells were exposed to PSCs [7]. In addition, interactions between the tumor and surrounding stromal cells have been linked with tumorigenesis, metastasis, and an increased expression of cancer stem cell-related genes [6,33].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic stellate cells (PSCs) are primarily responsible for the desmoplastic response observed in pancreatic cancer [7,8]. PSCs are myofibroblast-like cells residing in the periacinar spaces that are typically quiescent under normal physiological conditions, but can become activated in response to pancreatic injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation